Keterikatan Kerja dan Kepemimpinan Transaksional Terhadap Kepuasan Kerja Layanan Publik dengan Keadilan Organisasi Sebagai Variabel Moderasi - Junita, Audia; Ni Bulan, Tapi Rondang; Lubis, Muhammad Al Hafis (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
This study aims to analyze: (1) the influence of work engagement and transactional leadership on public service worker satisfaction, (2) the influence of work engagement on public service worker satisfaction moderated by organizational justice, and (3) the influence of transactional leadership on public service worker satisfaction moderated by organizational justice. The study was conducted at the Tirtanadi Medan Regional Drinking Water Company (PDAM Tirtanadi Medan), one of the Regional-Owned Enterprises in the North Sumatra Provincial Government that serves the drinking water needs of the community. The type of explanatory research with a quantitative approach. The population of this study was PDAM Tirtanadi Medan, totaling 266 people, and a sample of 144 people based on calculations using the Slovin formula. Proportional random sampling was used in determining the sample. Primary data collection was carried out by distributing questionnaires. Data were analyzed using multiple regression methods and Moderated Regression Analysis. The results of the study prove that: (1) work engagement and transactional leadership have a significant effect on public service worker satisfaction with a large effect of 27.4%, (2) work engagement does not have a significant effect on public service worker satisfaction moderated by organizational justice, (3) likewise transactional leadership does not have a significant effect on public service worker satisfaction moderated by organizational justice. The organizational justice variable does not act as a moderating variable in this study. The dimensions of organizational justice that contribute to low job satisfaction are procedural and interactional justice.